O papel do exercício físico aeróbio na prevenção das alterações do sistema nervoso central em modelo animal de sepse - Bussmann, Regina Maldonado (2016)
Introduction: Sepsis is determined as a sistemic inflamatory response syndrome (SIRS) followed by an infecction, evidenced or not. Even after discharge, sepsis survivors have high mortality index and may develop long term cognitive impairment. Articles show that exercise act positively on cognitive behavior considering angiogenesis, neurogenesis and sinaptogenesis as well as like atennuation on memory dammage by depleted or downregulation of MDA and carbonils in hipocampos and córtex préfrontal córtex. Objetive: The aim of this study was analise the effects of moderate physical exercise treadmill program on preventions of alterations on CNS in an sepsis animal model. Methodology: This study use black male mice C57BL/6 (28 days, between 20-25 g). The animals were submitted to moderate physical exercise treadmill program during 8 weeks. Completing 88 days before sepsis induccion by LPS were aleatorally distribueted in groups(n = 10): 1) PBS + not exercitaded; 2) PBS + exercitaded; 3) LPS + not exercitaded; 4) LPS + exercitaded. After 10 days mice did the memory tests and after executed, and having samples of córtex pré-frontal, estriatum, hipocampus, cerebellum and córtex to avaliations based on levels of MDA, carbonils and free-thios. Results: The LPS + exercited didn’t show long term cognitive impairmentand and show smaller MDA concentrations on córtex total, hipocampus, estriatum e cerebellum; downregulated carbonils in córtex total and hipocampus and upregulated levels of free thiois in córtex pré-frontal e córtex total, when compared to LPS + not exercited group. Conclusions: Beyond performance of this training program was observed that memory and learning were preserved was partially explain for the bioquimics results when compared to not exercised group. We suggest new researches to verify how exercise effects may influence other patterns to better understand the power of this intervention Sugerem-se novas pesquisas para verificar a atuação do exercício em outras vias e cascatas metabólicas e compreender melhor o alcance desta intervenção.